LY2495655, an antimyostatin antibody, in pancreatic cancer: a randomized, phase 2 trial. Issue 5 (27th July 2018) - Golan, Talia; Geva, Ravit; Richards, Donald; Madhusudan, Srinivasan; Lin, Boris Kin; Wang, Haofei Tiffany; Walgren, Richard A.; Stemmer, Salomon M.
Abstract: Background: Cachexia is a formidable clinical challenge in pancreatic cancer. We assessed LY2495655 (antimyostatin antibody) plus standard‐of‐care chemotherapy in pancreatic cancer using cachexia status as a stratifier. Methods: In this randomized, phase 2 trial, patients with stage II–IV pancreatic cancer were randomized to 300 mg LY2495655, 100 mg LY2495655, or placebo, plus physician‐choice chemotherapy from a prespecified list of standard‐of‐care regimens for first and later lines of care. Investigational treatment was continued during second‐line treatment. The primary endpoint was overall survival. Results: Overall, 125 patients were randomized. In August 2014, 300 mg LY2495655 was terminated due to imbalance in death rates between the treatment arms; in January 2015, 100 mg LY2495655 treatment was terminated due to futility. LY2495655 did not improve overall survival: the hazard ratio was 1.70 (90% confidence interval, 1.1–2.7) for 300 mg vs. placebo and 1.3 (0.82–2.1) for 100 mg vs. placebo (recommended doses). Progression‐free survival results were consistent with the overall survival results. A numerically higher hazard ratio was observed in patients with weight loss (WL) of ≥5% (cachexia) than with <5% WL within 6 months before randomization. Subgroup analyses for patients stratified by WL in the 6 months preceding enrollment suggested that functional responses to LY2495655 (either dose) may have been superior in patients with <5% WL vs. patients with ≥5% WL. Among possibly drug‐related adverse events, fatigue, diarrhoea, and anorexia were more common in LY2495655‐treated than in placebo‐treated patients. Conclusions: In the intention‐to‐treat analysis, LY2495655 did not confer clinical benefit in pancreatic cancer. Our data highlight the importance of assessing survival when investigating therapeutic management of cachexia and support the use of WL as a stratifier (independent of performance status).